The Effect of Zoledronic Acid Injection on the Effectiveness of Chitosan-Coated Ursolic Acid Niosomes for Treating Liver Damage in NDEA-Induced Mice - Andang Miatmoko; Dwi Nur’aini Hidayati Hidayati; Dinda Chaerani; Berlian Sarasitha Hariawan; Devy Maulidya Cahyani; Liew Kai Bin; Esti Hendradi; Retno Sari (Berkala Ilmiah Kimia Farmasi, 2026)
Background: Ursolic Acid (UA) is well known as a BCS class IV terpenoid with anticancer, anti-inflammatory, and antioxidant properties. Niosomes have been reported to improve the bioavailability of poorly water-soluble drugs, and chitosan coating may further increase the bioavailability and liver accumulation. However, macrophage-mediated nanoparticle uptake may affect it. This study aimed to determine the effect of macrophage depletion on the therapeutic and preventive efficacy of chitosan-coated Nio-UA against the hepatotoxic effects of N-nitrosodiethylamine (NDEA) in mice. Methods: Nio-UA was prepared by thin-layer hydration and coated with chitosan via vortexing. In the curative therapy model, mice received NDEA (25 mg/kgBW, intraperitoneally) weekly for 6 weeks, followed by Nio-UA (11 mg/kgBW, orally) every 2 days for 8 doses. In the preventive model, mice were given Nio-UA at the same dose 7 and 3 days before NDEA induction, then weekly with NDEA for 4 weeks. Macrophage depletion was induced with zoledronic acid (ZOL) at a dose of 40 μg/mouse intravenously for 3 days. Results: Chitosan coating increased the niosomal particle size and polydispersity index (PDI) while modifying the ζ-potential. In vivo bilirubin levels differed significantly between the healthy and negative control groups, whereas albumin levels showed no significant difference. ZOL treatment did not significantly alter bilirubin or albumin levels compared to non-ZOL groups in either model. Discussions: The UA niosomes therapy did not significantly improve serum albumin or total bilirubin levels after ZOL injection, suggesting that the ZOL dose injection may have not substantially affect niosome uptake. The effectiveness of macrophage depletion needs further validation. ZOL injection slightly reduced bilirubin levels in the preventive therapy model, may indicate partial depletion of hepatic macrophages and decreased hepatic clearance of Nio-UA and Nio-UA-Cs. These preliminary findings provide a basis for further investigation whether ZOL injection can increase the UA's therapeutic effectiveness. Conclusions: In this exploratory study, ZOL injection did not markedly improve the therapeutic effectiveness of chitosan-coated Nio-UA in preventing or treating the hepatotoxic effects of N-nitrosodiethylamine (NDEA) in mice. Further studies for validating macrophage depletions are required to clariy the mechanism.   Keywords: Cancer, Macrophage Depletion, Ursolic Acid, Niosomes, Hepatotoxic Effects, N-nitrosodiethylamine